EARNED VALUE ANALYSIS FOR COST AND TIME EFFICIENCY ON THE BONDOWOSO POLIJE CAMPUS ADMINISTRATION BUILDING PROJECT - Irniawan, Dodik; Oetomo, Wateno; Marleno, Risma (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2024)
The problem in the implementation of the Bondowoso Polije Campus Administration Building Project is the limited cost and time available. With a 5 (five) storey building design with a reinforced concrete structure, each floor of which has an area of 240 m2 with a total floor area of almost 1440 m2, this building is a fairly complex building, in terms of the function of the building itself. The contract value of physical work amounted to Rp. 5,599,873,601.60 and was carried out within 120 days or 18 weeks. This research method uses Earned Value Method. From the analysis, results and discussion of the Bondowoso Polije Campus Administration Building project, the main conclusion is that there are variations in cost and time during the project period, with the lowest value of Cost Variation reaching (-)Rp 228,191,016.04 in week 7. Although the Cost Productivity Index (CPI) showed positive and negative variations, with a low of 0.672 in week 7, the Time Productivity Index (SPI) was always < 1, reaching a final value of 0.663. The estimated cost (EAC) to complete the project is IDR 5,993,156,919.70, while the estimated total work time (EAS) of the project is 20.543 weeks. Overall, the project is expected to experience a delay of 2.543 weeks and a cost loss of Rp 393,323,318.10.